Effectiveness of Dialkyl Carbamoyl Chloride (DACC)-Coated Dressings in Reducing Surgical Site Infections and Promoting Wound Healing: A Randomized Controlled Trial - Dr Priyanka sekar; Dr Manoj Kumar; Dr J Sharath Kumar, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Surgical site infections (SSIs) are a significant cause of morbidity, mortality, and extended healthcare costs following surgery. Effective prevention strategies are essential to reduce the risk of SSIs. This study evaluates the effectiveness of dialkyl carbamoyl chloride (DACC)-coated dressings in reducing SSIs, promoting faster wound healing, and improving patient comfort compared to traditional non-coated dressings. Methods: A prospective, randomized controlled trial was conducted with 100 patients undergoing elective abdominal, orthopedic, or vascular surgery. Patients were randomly assigned to either the DACC-coated dressing group (n = 50) or the control group (traditional non-coated dressings, n = 50). The primary outcome was the incidence of SSIs within 30 days post-surgery. Secondary outcomes included time to healing, bacterial load at Day 1 and Day 7 post-surgery, and patient-reported pain scores at Days 2, 7, and 14 post-surgery. Bacterial cultures and visual analogue scale (VAS) scores were used to assess infection and pain levels. Results: The incidence of SSIs was significantly lower in the DACC-coated group (6%) compared to the control group (14%) (p < 0.05). The average time to healing was 10 days in the DACC-coated group, compared to 12 days in the control group. Bacterial load at Day 1 was lower in the DACC-coated group (5.5 CFU/mL) compared to the control group (7.8 CFU/mL), and by Day 7, the DACC-coated group showed a greater reduction in bacterial load (1.2 CFU/mL vs. 3.5 CFU/mL). Pain scores were also significantly lower in the DACC-coated group, with an average VAS score of 2.1 at Day 2 and 1.3 at Day 7, compared to 3.7 at Day 2 and 2.9 at Day 7 in the control group. Conclusions: DACC-coated dressings significantly reduce the incidence of SSIs, promote faster wound healing, reduce bacterial load, and alleviate pain compared to traditional non-coated dressings. These findings suggest that DACC-coated dressings can be an effective tool in enhancing surgical wound care and preventing SSIs, offering a promising option for post-operative management, particularly in high-risk surgical patients. Further studies are needed to confirm the long-term benefits and cost-effectiveness of DACC-coated dressings.